(untitled) (Malaysia, 1992)
Aquaculture loses millions of dollars in revenue annually due to aquatic animal diseases. Disease outbreaks continue to threaten profitable and viable aquaculture operations throughout the world. As a result, aquaculture biosecurity programs that address aquatic animal pathogens and diseases have become an important focus for the aquaculture industry.
Keywords: Aquaculture,Shellfish,Fishes,Fishes; Diseases,Diseases,Parasites; Asia,Asia,Asia,Asia